Empirical Determinants of Saving in Islamic Banks at Tasikmalaya City - Ayif Fathurrahman; Fahmi Zulfikar (Universitas Muhammadiyah Malang, 2020)
This study aims to analyze several factors that influence public interest in saving in Islamic banks in the City of Tasikmalaya. These factors are location, knowledge, facilities, and promotions. This study uses primary data by giving questionnaires to the people of Tasikmalaya City, with a total sample 100 respondents. The method used was Multiple Linear Regression. Based on the analysis that has been done. The results found that the variable of location, knowledge, and promotion have a significant and positive effect on the community’s interest of saving in Islamic banks at Tasikmalaya, but the facility variable have not significant effect on the community’s interest in saving.